1979
DOI: 10.1111/j.2044-8295.1979.tb01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Interocular transfer of movement after‐effects in schizophrenia

Abstract: A group of 16 chronic schizophrenic subjects were compared with 15 age-matched control subjects for interocular transfer of movement after-effects. Contrary to the hypothesis that schizophrenic subjects would show a deficit on this measure schizophrenics showed increased transfer compared to the controls. This effect is not due to response perseveration and is not correlated with length of hospitalization, age or dose of antipsychotic drugs. It is suggested that the effect reflects a deficit in 'inhibitory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Few studies have manipulated these parameters within a single experiment; however, differences in parameter values may explain discrepancies across studies. Of those studies comparing the duration of movement aftereffects between schizophrenia and healthy controls, two studies reported longer aftereffect durations in schizophrenia (Abraham and McCallum, 1973;Claridge, 1960), five studies reported null findings (Herrington and Claridge, 1965;Hersen et al, 1972;Krishnamoorti and Shagass, 1963;Schein, 1960;Tress and Kugler, 1979), and no studies observed longer durations in controls. With the aforementioned caveat regarding null findings in mind, it is nevertheless interesting that those studies reporting greater duration of the movement aftereffect in patients used relatively long adapter durations (1 minute), whereas those that reported null results used shorter adapter durations (15-30 seconds).…”
Section: Critical Review Of Findings In Schizophreniamentioning
confidence: 99%
“…Few studies have manipulated these parameters within a single experiment; however, differences in parameter values may explain discrepancies across studies. Of those studies comparing the duration of movement aftereffects between schizophrenia and healthy controls, two studies reported longer aftereffect durations in schizophrenia (Abraham and McCallum, 1973;Claridge, 1960), five studies reported null findings (Herrington and Claridge, 1965;Hersen et al, 1972;Krishnamoorti and Shagass, 1963;Schein, 1960;Tress and Kugler, 1979), and no studies observed longer durations in controls. With the aforementioned caveat regarding null findings in mind, it is nevertheless interesting that those studies reporting greater duration of the movement aftereffect in patients used relatively long adapter durations (1 minute), whereas those that reported null results used shorter adapter durations (15-30 seconds).…”
Section: Critical Review Of Findings In Schizophreniamentioning
confidence: 99%
“…A handful of early studies measuring the duration or strength of these aftereffects in patients with schizophrenia (reviewed in Harris, 1994), have yielded conflicting findings. These include slower aftereffect build-up (Abraham and McCallum, 1973;Claridge, 1960;Herrington and Claridge, 1965), no difference in aftereffect duration (Tress and Kugler, 1979), and reduced aftereffect strength (Kelm, 1962(Kelm, , 1968Wertheimer, 1954;Wertheimer and Jackson, 1957). Discrepant findings across studies have been attributed to a combination of medication use, as antipsychotics reduce visual aftereffect duration in healthy individuals (Harris et al, 1986;Harris et al, 1983), clinical status, and mode of measuring aftereffects (Harris, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, Gulman et al (1982) found that SEP transmission time was decreased from left to right hemisphere, suggesting directional loss of inhibition. Similarly, Tress et al (1979) found a large discrepancy between left ipsilateral and contralateral SEPs present in normal subjects, but not in schizophrenics. Both of these findings are consistent with the relative increase in right-to-left-hand transfer errors in the schizophrenic subjects of the present study.…”
Section: Discussionmentioning
confidence: 75%
“…The basic procedure for this test has been described in Tress and Kugler (1979). The stimulus disc was 24 in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation